Анализ АЧХ аналоговых электронных устройств на операционных усилителях с внутренней коррекцией - Белущенко, А. В. (ХНУРЭ, 2012)
By means of the generalized counts of a signal have been obtained expressions for transfer functions at four variants of switching on of operational amplifiers and comparison o f their gain-frequency characteristics has been made